Does Similarity in Philippine FTAs Matter in Trade? - Francis Mark A. Quimba; Mark Anthony A. Barral (Philippine Institute for Development Studies (PIDS), 2022)
To understand the design of JPEPA and EFTA, notably the similarities with other FTAs of Japan and EFTA-member countries, respectively, and how these similarities affect Philippine trade, the study proposes the use of text-of-trade-analysis, that is, text analysis employing textas-data. The paper demonstrates the application of text analysis to complement the conventional methods of assessing the impacts of trade agreements. The results reveal that similarity across trade agreements, both at document and chapter or topic-specific provisions (such as trade in goods and rules of origin or strong references to sustainable development) may influence and encourage trade.
Keywords: 330; EFTA-PH FTA; Cosine LSA; Export; Jaccard; Free Trade Agreements; PJEPA; Non-Tariff Measures; Rules of Origin; Sustainable Development; Text Analysis; Similarity; Trade in Goods